Üniversite öğrencilerinin fiziksel aktivite yapma durumu ve fiziksel aktivitenin kalp sağlığına etkisini bilme durumu - OĞUZ, SIDIKA; ÇAMCI, GÜLŞAH (My University, 2018)
AraĢtırma üniversite öğrencilerinin fiziksel aktivite yapma durumları ve fiziksel aktivitenin kalp sağlığına etkisini bilme durumunu belirlemek amacıyla kesitsel ve tanımlayıcı bir çalıĢma olarak planlandı. Ekim 2014-ġubat 2015 tarihleri arasında, bir üniversitenin Sağlık Bilimleri Fakültesi ve Sosyal Bilimler Fakültesinde öğrenim gören ve araĢtırmaya katılmayı kabul eden 602 öğrenci çalıĢmanın örneklemini oluĢturdu. 26 soruluk bir anket formu ile veriler toplandı. Ġstatiksel analizler için yüzdelik, frekans, ortalama ve ki-kare testleri kullanıldı. Tüm testlerde anlamlılık seviyesi p< 0,05 olarak ele alındı. YaĢ ortalaması 20,04±1,87 olan olguların %69,3‘ ü kız olup, %63‘ü Sağlık Bilimleri Fakültesi‘nde öğrenim görmektedir. ÇalıĢmada erkek öğrencilerin kız öğrencilere göre daha aktif olduğu (p=0,001) ve erkeklerin fiziksel aktivite yapma nedenleri; baĢkalarıyla tanıĢmak ve eğlence için yaptığı belirlendi (p=0,001). Kızların erkeklere göre aktiviteyi kilo vermek veya kilosunu korumak için yaptığı saptandı (p=0,006). Kız öğrencilerin zamanı olmadığı için (p=0,001) erkek öğrencilerin ise maddi gücü yeterli olmadığı için aktivite yapmadığı belirlendi (p=0,019). Kız öğrencilerin erkek öğrencilere göre fiziksel aktivitenin kalp sağlığına olumlu etkisi olduğunu daha fazla bildiği bulundu (p=0,003). AraĢtırmada sağlık bilimleri öğrencilerinin sosyal bilimleri öğrencilerine göre fiziksel aktivitenin kalp sağlığı üzerinde olumlu etkiye sahip olduğu düĢüncesinin daha fazla olduğu saptandı (p=0,001).

The study was planned as a cross-sectional and descriptive study to determine the status of university students' physical activity and the effect of physical activity on heart health. 602 students who volunteered to participate in the study of simple selected students, studied at Faculty of Health Sciences and Faculty of Social Sciences of a university between October 2014-February 2015. Data were collected with using a questionare of 26 questions. For statistical analysis, percentage, frequency, mean and chi-square were used. The level of significance was considered p <0.05 in all tests. The average age of the students was 20.04 ± 1.87, %69.3 of the subjects were women and 63% of them were studying in the Faculty of Health Sciences. At the research, it was determined that male students were more active (p=0.001) than female students and male student did this for entertainent and meeting new people. (p=0.001). It was found that women performed activities to lose weight or to protect weight according to men (p =0.006). It was determined that female students did not perform activities to have no time (p =0.001) and male student did not do activities to have insufficient financial power (p =0.019). lt was found that female students knew more positive impact on heart health of physical activity than male students (p =0.003). In the study, it was found that the health sciences students had more positive effects of physical activity on heart health than the social sciences students (p =0.001).
State of university students' physical activity and knowing the effect of physical activity on heart health
Keywords: Üniversite Öğrencileri; Fiziksel Aktivite; Kalp; University Students; Physical Activity; Heart